Formation of Socially Successful Personality of Adolescent Pupils by Means of Gamification (Kyiv City, Ukraine) - Necherda, Valeriia; Bezruk, Kateryna; Petrochko, Zhanna; Kyrychenko, Valentyna; Denysiuk, Olena (International Journal of Research in E-learning, 2024)
The research highlights the essence of gamification and the approbation of the curriculum with elements of gamification "Social successfulness" in the educational process of educational institutions. Theoretical methods are applied – analysis, synthesis, comparison, systematization, generalization of materials from psychological and pedagogical sources regarding the problem of social successfulness and the possibilities of its formation in adolescents in the conditions of out-of-school and general secondary education institutions, specification for harmonizing the content of the curriculum "Social successfulness" and its process approvals; empirical methods – observation, questionnaires for collecting empirical information, blitz surveys concerning the awareness of the characteristics of a successful personality. The authors consider gamification as a set of various tools and mechanics that contribute to the significant enrichment of the educational process with entertaining, educational, educational, motivational, and social-communicative components. The researchers characterized the educational program "Social successfulness", in particular, determined its target orientations and key competencies of teenagers, highlighted the gamification tools necessary for the implementation of the program, found out that the mixed format is the optimal format for its implementation, as it combines the advantages of offline and online learning and can be effective in conditions of increased danger associated with martial law. The article carried out a pedagogical reflection and found out that, according to the results of the blitz survey, teenagers verbalize the two most common portraits of a socially successful personality (based on external indicators of success and personal qualities), according to the results of the questionnaire, the majority of respondents positively perceived game tools and recognized her own activity during training with the use of gamification as productive. The issue of using gamification tools for children of different ages, including those with special educational needs, and the creation of an algorithm for using gamification elements in various educational institutions require further research.